Anion-driven tetrel bond-induced engineering of lead(ii) architectures with N′-(1-(2-pyridyl)ethylidene)nicotinohydrazide: experimental and theoretical findings. Issue 1 (8th December 2016) - Mahmoudi, Ghodrat; Safin, Damir A.; Mitoraj, Mariusz P.; Amini, Mojtaba; Kubicki, Maciej; Doert, Thomas; Locherer, Franziska; Fleck, Michel
Abstract : A new series of Pb II coordination compounds was assembled with the N ′-(1-(2-pyridyl)ethylidene)nicotinohydrazide ligand and various auxiliary inorganic counterions. Abstract : The evaluation of N ′-(1-(2-pyridyl)ethylidene)nicotinohydrazide (HL ) as a linker for the Pb II tagged extended structures is described. The reaction of Pb(ClO4 )2 or Pb(OAc)2 withHL in MeOH at 60 °C and room temperature, respectively, leads to heteroleptic complexes{[PbL]ClO4 } n · n H2 O and[PbL(OAc)]2, while the same reaction of Pb(ClO4 )2 withHL at 60 °C in the presence of two equivalents of NaOAc or NaNO2 leads to heteroleptic complexes{[Pb(HL)(OAc)]ClO4 } n and[PbL(NO2 )] n, respectively. Using Pb(NO3 )2 as a source of Pb II in the same reaction withHL and two equivalents of NaN3 or NaNCS at room temperature yields[PbLN3 ] n and[Pb2 (HL)2 (NO3 )2 (NCS)2 ], respectively. The room temperature reaction of Pb(NO3 )2 withHL in the presence of two equivalents of NaClO4 leads to the transformation of the parent ligand to its perchlorate salt[H2 L]ClO4 . In all the obtained Pb II structures, HL or its deprotonated formL acts both as a chelating and a bridging ligand. The nature of the inorganic anion also influences the final structure. In all complexes the Pb II center exhibits a hemidirected coordination geometry with all the covalent bonds being concentrated on one hemisphere of the coordination sphere with the closest approach of two atoms on the other side varying from 151° to 232°. The sterically available Pb II ion participates in tetrel bonding as evidenced from the detailed structural analysis of the described complexes. As a result of tetrel bonding, the structures of all the six compounds can be extended to a higher dimensional framework, which is further stabilized by π⋯π stacking interactions between the aromatic rings. The DFT based charge and energy decomposition (ETS-NOCV) calculations are performed in order to shed light on the nature of non-covalent interactions that determine the stability of the obtained structures.